The impact of financial ratio towards performance domestic bank in Malaysia after merger and acquisition / Siti Fatimah Hassim - Hassim, Siti Fatimah (Faculty of Business Management, 2017)
During the Asian financial crisis in year 1997, countries under International Monetary Fund (IMF) programmes are required to close down the small and weakest banking institutions. However, Malaysia government denied and initiated a robust bank merger programme to restructure all the fifty four institutions into ten anchor banks in year 1999. However, the impact of the merger and acquisition of Malaysian bank is still vague. Hence, this paper attempts to examine the impact of the merger and acquisition using financial ratio. This paper focuses on several domestic bank in Malaysia which involved in merger and acquisition before year 2010. This paper uses descriptive statistic to find financial ratio and performance of domestic banks in Malaysia after 6 years merger and acquisition to identify the impact. Besides, regression analysis used to determine the relationship of independent variables which are Net Profit Margin, Current Ratio, Total Asset Turnover, Debt Ratio and Earning Per Share with Return On Asset as dependent variable.